Kesiapan Lulusan Pendidikan Kesetaraan Paket C dalam Menghadapi Dunia Kerja (Studi Kasus PKBM Tutwuri Handayani Palembang) - Andhani, Meri; Shomedran, Shomedran (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2023)
The purpose of this study is to find out how the readiness of equality education graduates package C in facing the world of work (Case Study at PKBM Tut Wuri Handayani Palembang). This research uses a qualitative approach with interview, observation, and documentation data collection techniques. The data analysis used in this study is data reduction, data presentation, and drawing conclusions. The results of this study show 1) cognitive readiness of problem solving graduates given during learning Package C, namely by learning mathematics by discussing and reading books, graduates' ability to see opportunities is obtained through a friendship environment, social media, understanding learning materials knowledge gained by students through books and learning taught by tutors, that the lack of activeness of package C students in participating in learning, creative thinking by opening businesses and running special programs in their work. 2) Affective interest they can work as permanent employees. However, with the attitude and feeling they have that with a fairly high competition, there are still those who are unemployed or just as day laborers. 3) Psychomotor, which consists of the response of graduates in facing the world of work with effort and accepting that competition and challenges in the world of work will always exist and graduates who have psychomotor readiness start from attending training, skills that graduates can develop when entering the world of work 4) communication skills effectively are very important, because in finding a job, you have to find a lot of information and communicate with each other with friends or people you just met, skills in the business field by attending training from outside parties, such as skills in product marketing, making crafts, training and training in the PKK program